THE ELEMENTS OF PERSONALITY IN THE MAIN CHARACTER OF SWEENEY TODD: THE DEMON BARBER OF FLEET STREET BY TIM BURTON - Rizki Syifaurrahman; Ujang Suyatman (CALL, 2019)
This research analyzes the elements of personality in the main character of Sweeney Todd: The Demon of Barber of Fleet Street by Tim Burton. The researcher uses descriptive qualitative methods because the results of this research are words which are then described. In this research, the reseacher found the elements of personality in the main character of Sweeney Todd: The Demon of Barber of Fleet Street by Tim Burton such as Todd id as the desire wants to revenge Turpin and Beadle because of what they did to Todd’s family, the desire wants to kill Pirelli because he knew his the real identity, and the desire wants to kill Mrs. Lovett because she lied him. The desires as Todd’s id realized and supported by the ego. The way how ego realized all of id in Sweeney Todd, the ego does his role with an action. Thus the superego does not appear much as the id. His role only related with a good value such as when Todd wants to reveal the fake barber about his crime.Keywords: Sweeney Todd, id, ego, superego.